Tannase improves gallic acid bioaccessibility and maintains the quality of mango juice. (2nd September 2018) - Sirven, Maritza A.; Negrete, Marcos; Talcott, Stephen T.
Summary: The effect of tannase on gallic acid (GA) bioaccessibility and auto‐oxidative browning of mango juice was investigated. After 2 h of simulated gastric digestion, the concentration of bioaccessible GA increased ( P  < 0.05) 94.3 ± 7.0% in juice treated with 0.5 U mL −1 tannase while juice not treated with tannase had only a 6.3 ± 3.4% increase in GA. During 2–10 h of simulated intestinal digestion, tannase treated juice continued to have a higher concentration ( P  < 0.05) of bioaccessible GA in comparison to juice that was not treated with tannase. The use of 167 U 100 mL −1 tannase while processing mango juice did not result in any differences ( P  < 0.05) in browning measured at 420 nm, yet there was significantly higher ( P  < 0.05) GA in mango juice post‐storage. Processing mango juice with tannase can help improve the bioaccessibility of mango polyphenols without hindering the quality of juice during storage. Abstract : The use of tannase in mango juice increases polyphenols post‐processing and polyphenol bioaccessibility in vitro. Tannase also does not negatively impact mango juice quality.